2012
DOI: 10.1038/bjc.2012.343
|View full text |Cite
|
Sign up to set email alerts
|

Safety, cost-effectiveness and feasibility of daycase paracentesis in the management of malignant ascites with a focus on ovarian cancer

Abstract: Background:Paracentesis for malignant ascites is usually performed as an in-patient procedure, with a median length of stay (LoS) of 3–5 days, with intermittent clamping of the drain due to a perceived risk of hypotension. In this study, we assessed the safety of free drainage and the feasibility and cost-effectiveness of daycase paracentesis.Method:Ovarian cancer admissions at Hammersmith Hospital between July and October 2009 were audited (Stage 1). A total of 21 patients (Stage 2) subsequently underwent par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…PC brings immediate but temporary relief in 78%–90% of cases, and implies multiple hospitalizations 2,10,17. This approach is undertaken in hospital, as a day-case or inpatient procedure 18. Patients often wait until fluid accumulation is substantial to avoid frequent hospital stays, and to ensure the ascites is amenable to drainage, resulting in a deterioration in their quality of life (QOL) 16…”
Section: Introductionmentioning
confidence: 99%
“…PC brings immediate but temporary relief in 78%–90% of cases, and implies multiple hospitalizations 2,10,17. This approach is undertaken in hospital, as a day-case or inpatient procedure 18. Patients often wait until fluid accumulation is substantial to avoid frequent hospital stays, and to ensure the ascites is amenable to drainage, resulting in a deterioration in their quality of life (QOL) 16…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous fluid replacement was not performed as part of our drainage protocol. Previous studies have suggested that free drainage of malignant ascites is safe and not associated with significant hypotension . The use of intravenous fluids including albumin infusions is not routinely recommended during or after paracentesis for malignant ascites .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that free drainage of malignant ascites is safe and not associated with significant hypotension. 13,14 The use of intravenous fluids including albumin infusions is not routinely recommended during or after paracentesis for malignant ascites. 15 Patients in only two of the six studies of peritoneal ports received intravenous albumin.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…Eight grams of albumin in 20% solution per litre drained, immediately after completing the procedure, is a common recommendation . There are no data to support volume expansion with albumin following therapeutic drainage of malignant ascites …”
Section: Introductionmentioning
confidence: 99%
“…However, it is generally accepted that one total paracentesis is safer than repeated paracenteses, provided volume expansion is administered to cirrhotic patients . A patient requiring therapeutic paracentesis should be quickly drained in a single session, ideally over 1–4 h with a drain dwell time no longer than 6 h …”
Section: Introductionmentioning
confidence: 99%